Upaya Peningkatan Kemampuan Bahasa Anak Usia 4-5 Tahun melalui Kegiatan Menceritakan Kembali Isi Cerita di Kelompok Bermain Aisyiyah Gobah Kecamatan Tambang - Mohammad Fauziddin (LPPM Universitas Pahlawan Tuanku Tambusai, 2017)
The aim of this research is to know the improvement of children's language ability through the activity of retelling the story content in children aged 4-5 years in Aisyiyah Gobah Tambang Bermain (KB). The problem faced was still low ability of early childhood language. The method of this research was classroom action research. The instrument of this research consists of observation sheet of improvement of language ability of children. Research subjects are children aged 4-5 years amounted to 18 people. The result of the research was found, before the action, the ability of the children's language in the activity of retelling the children's story content was the BB (44%) of the MB (38%) BSH (18%) and the BSB only (5.5%). After the first cycle of 1 child meeting the BB (25%) the MB (30%) BSH (16%) and the BSB only (8%). Cycle I meeting 2 children who were BB (22%) who MB (44%) BSH (22%) and the BSB only (11%). Cycle II meetings 1 cycle II children who are BB (11%) are MB (36%) BSH (38%) and B only (13%). Cycle II The 2nd meeting of the children who were BB (8%) were MB (16%) BSH (55%) and the BSB (16%). Thus it can be concluded that the child's language skills can be improved through the activities of retelling the contents of the story of children aged 4-5 years in Aisyiyah Gobah group sub-district Tambang.